Promoção de Saúde no Sistema Penitenciário: Atuação do Psicólogo - LILÉIA SOUZA LEITE (2021)
The National Policy for Comprehensive Health Care for People Deprived of Liberty in the Prison System (PNAISP) enables new practices for Psychologists in prisons. Coming from working as experts in criminological examinations, preparing reports and validating suitability for sentence progressions, working through Psychosocial Intervention is something under construction in these institutions. This research aims to understand the Psychologist's role in promoting health in penal units in the city of Campo Grande-MS, with theoretical and methodological assistance and support using Foucauldian tools. The interview was used as a data collection technique, applied to seven professionals who work in different prisons based on the following questions: How have psychology professionals performed in the field of health in the prison system? What are the difficulties encountered? The results of this study point to numerous challenges (unhealthy environment, prison overcrowding, lack of professionals, among others) with some considerations that, in this journey and detours, it is understood that working with health promotion does not ensure that psychologists break with discourses and practices producers and maintainers of knowledge-powers, but one of the tools for the exercise of biopolitics, involving the subject, social practices and cultural determinants, producing conditions for their subjection to penalties, putting mental health at risk, in the vacuum of laws, rules and norms in prison institutions, thus guaranteeing their survival and the limits of these relationships in the work of psychology professionals.